2019
DOI: 10.3390/v11060499
|View full text |Cite
|
Sign up to set email alerts
|

Genistein Has Antiviral Activity against Herpes B Virus and Acts Synergistically with Antiviral Treatments to Reduce Effective Dose

Abstract: Herpes B virus is a deadly zoonotic agent that can be transmitted to humans from the macaque monkey, an animal widely used in biomedical research. Currently, there is no cure for human B virus infection and treatments require a life-long daily regimen of antivirals, namely acyclovir and ganciclovir. Long-term antiviral treatments have been associated with significant debilitating side effects, thus, there is an ongoing search for alternative efficacious antiviral treatment. In this study, the antiviral activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 37 publications
0
27
0
1
Order By: Relevance
“…They have reported the antiviral activity of genistein against herpes B virus, and also revealed that it targets the virus after the viral replication stage. Moreover, its combination with the acyclovir and ganciclovir proved to be effective with the reduction of effective dose (LeCher et al 2019). Similarly, genistein has been reported to possess antiviral activity against HSV-1, cytomegalovirus, and bovine herpesvirus-1, SV40, human papilloma virus, porcine reproductive and respiratory syndrome virus, African swine fever virus, and HIV (LeCher et al 2019).…”
Section: Flavonoids As Antiviral Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…They have reported the antiviral activity of genistein against herpes B virus, and also revealed that it targets the virus after the viral replication stage. Moreover, its combination with the acyclovir and ganciclovir proved to be effective with the reduction of effective dose (LeCher et al 2019). Similarly, genistein has been reported to possess antiviral activity against HSV-1, cytomegalovirus, and bovine herpesvirus-1, SV40, human papilloma virus, porcine reproductive and respiratory syndrome virus, African swine fever virus, and HIV (LeCher et al 2019).…”
Section: Flavonoids As Antiviral Agentsmentioning
confidence: 99%
“…Moreover, its combination with the acyclovir and ganciclovir proved to be effective with the reduction of effective dose (LeCher et al 2019). Similarly, genistein has been reported to possess antiviral activity against HSV-1, cytomegalovirus, and bovine herpesvirus-1, SV40, human papilloma virus, porcine reproductive and respiratory syndrome virus, African swine fever virus, and HIV (LeCher et al 2019). Anti-simian rotavirus SA-11 activity of the ethanolic extracts was reported from the leaves of medicinal plant (Myracrodruon urundeuva), found in Brazil (Cecílio et al 2016).…”
Section: Flavonoids As Antiviral Agentsmentioning
confidence: 99%
“…Genistein was previously recognized to have some cellular actions including, glucose, lipid metabolism and other activities such as lipid peroxidation, inflammation, and fibrosis [28][29][30] as well as its antiviral activity against Herpes B Virus [31] and chondroprotective Effects against osteoarthritis [32].…”
Section: Discussionmentioning
confidence: 99%
“…164 It also prevented plaque formation of Herpes B virus and reduced virus production. 165 It was reported to show some efficacy against H1N1 influenza A virus. 166 Against human immunodeficiency virus type 1 (HIV-1), it caused cell cycle arrest in G2.…”
Section: Genisteinmentioning
confidence: 99%